FENOMENA SASTRA SUFISTIK DI ERA MODERN - Syaifuddin Syaifuddin (lp2m-uin malang, 2010)
According to the sociology of literature, the popularity of sufistic literature in Indonesia and Egypt in the 1980s until 1990s is more than the literary phenomena. It is the phenomena of social, politic, and culture. In order to understand that phenomena, works of literature should be put, firstly, as the most representative “space” for discourse of sufistic discourse, it is not only as the practical and literary movement but also religious, social, political and cultural movements. So, every sufistic literature becomes relevant and contextual toward its time. Secondly, the field of literature challenge can move by following the change of society, culture and civilization, this make sufistic literature to be put in that themes. Practicing the sufistic literature can transmit the preservation of divinity or principles of monotheism continously. We can understand that there is a relation between the phenomena of popularity of sufistic literature either in Indonesia or in Egypt and modernity. Sufistic literature tries to give reaction, response, and resistance to the modernism discourse generally and secularism or secularization specifically.